Requirements for Successful Education in the Maghreb Countries According to the United Nations Programme - Hamaizia, Lamia (Finance and Business Economies Review, 2022)
The paper aims to illustrate the reality of education in Maghreb countries (Algeria, Tunisia and Morocco) towards the requirements of the United Nations to achieve sustainable development, by focusing on comparing the characteristics of sustainable education; this later is one of many inputs of sustainable development, so we can consider it as one of important social variables of sustainable development. We have reached many results, among them: the efforts made by the three Maghreb countries in terms of education are more or less acceptable, especially in primary and secondary education, however the expected results are not up to all expectations.